2000
DOI: 10.1086/313928
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Elimination of Congenital Rubella Syndrome (CRS): Summary of a Workshop on CRS Elimination in the United States

Abstract: The goal of eliminating indigenous rubella and congenital rubella syndrome (CRS) in the United States in the near future is now within reach, because rubella incidence has been sustained at record-low levels since the mid-1990s. Effective prevention strategies to eliminate CRS and rubella require improvement in the surveillance of CRS and congenital rubella infection (CRI). The purpose of the workshop was to review rubella and CRS epidemiology, as well as current clinical, diagnostic, and laboratory practices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
1
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 28 publications
1
53
1
6
Order By: Relevance
“…Hearing impairment most frequently appears among the major complications of CRS, being observed in up to 96z of cases (3,13). However, the incidence of hearing impairment observed at diagnosis in this study, was as low as 25z.…”
Section: Discussioncontrasting
confidence: 54%
“…Hearing impairment most frequently appears among the major complications of CRS, being observed in up to 96z of cases (3,13). However, the incidence of hearing impairment observed at diagnosis in this study, was as low as 25z.…”
Section: Discussioncontrasting
confidence: 54%
“…2 Elimination goals have been set for Finland, the United States, and the English-speaking Caribbean, and rubella control in other regions of the Americas is a foreseeable goal. [3][4][5][6][7] The global picture is very different-only 28% of the developing countries routinely vaccinate against rubella. 8 Mathematic modeling has yielded congenital rubella syndrome disease burden estimates ranging from 110 000 to 308 000 per year.…”
Section: Introductionmentioning
confidence: 99%
“…1 CRI refers to all outcomes associated with intrauterine rubella infection, including miscarriage, stillbirth, a combination of birth defects, and asymptomatic infection. 2 Congenital rubella syndrome (CRS) refers to a CRI that occurs in various congenital defects (eg, deafness, cataract, and heart abnormalities). 2,3 Deafness is usually congenital, but a few cases of deafness after birth have been reported.…”
mentioning
confidence: 99%
“…2 Congenital rubella syndrome (CRS) refers to a CRI that occurs in various congenital defects (eg, deafness, cataract, and heart abnormalities). 2,3 Deafness is usually congenital, but a few cases of deafness after birth have been reported. 3,4 Papania et al 5 reported in 2014 that since 2004 the incidence of rubella in the United States was <1 per 10 000 000 individuals and that the incidence of CRS was <1 per 5 000 000 births.…”
mentioning
confidence: 99%